Effect of Type 2 Diabetes Mellitus on Left Ventricular Geometry and Systolic Function in Hypertensive Subjects: Hypertension Genetic Epidemiology Network (HyperGEN) Study - Palmieri, Vittorio; Bella, Jonathan N.; Arnett, Donna K.; Liu, Jennifer E.; Oberman, Albert; Schuck, Min-Yan; Kitzman, Dalane W.; Hopkins, Paul N.; Morgan, Derek; Rao, D. C.; Devereux, Richard B. (Circulation (New York, N.Y.), 2001)
Background —Type 2 diabetes is a cardiovascular risk factor. It remains to be elucidated in a large, population-based sample whether diabetes is associated with changes in left ventricular (LV) structure and systolic function independent of obesity and systolic blood pressure (BP). Methods and Results —Among 1950 hypertensive participants in the HyperGEN Study without overt coronary heart disease or significant valve disease, 20% (n=386) had diabetes. Diabetics were more likely to be women, black, older, and have higher BMI and waist/hip ratio than were nondiabetics. After adjustment for age and sex, diabetics had higher systolic BP, pulse pressure, and heart rate; lower diastolic BP; and longer duration of hypertension than nondiabetics. LV mass and relative wall thickness were higher in diabetic than nondiabetic subjects independent of covariates. Compared with nondiabetic hypertensives, diabetics had lower stress-corrected midwall shortening, independent of covariates, without difference in LV EF. Insulin levels and insulin resistance were higher in non–insulin-treated diabetics (n=195) than nondiabetic (n=1439) subjects (both P <0.01). Insulin resistance positively but weakly related to LV mass and relative wall thickness. Conclusions —In a relatively healthy, population-based sample of hypertensive adults, type 2 diabetes was associated with higher LV mass, more concentric LV geometry, and lower myocardial function, independent of age, sex, body size, and arterial BP. structural and functional abnormalities in addition to, and independent of, atherosclerosis. 13 14 In the Framingham cohort, diabetes was associated with higher LV mass in women but not men. 15 High blood pressure (BP), obesity, and abnormal lipid profile, which often coexist with diabetes, tend to be associated with preclinical cardiovascular abnormalities 16 and may contribute to the association of diabetes with cardiovascular events. Cardiac features of diabetic and nondiabetic hypertensive subjects remain incompletely described in population-based samples. Therefore, we compared clinical and metabolic characteristics, LV geometry, and systolic function between diabetic and nondiabetic hypertensive participants in the Hypertension Genetic Epidemiology Network (HyperGEN) Study.